3D printing of titanium matrix composites - Koh, Zhe Quan (Nanyang Technological University, 2022)
Titanium matrix composites (TMCs) refer to a titanium alloy matrix mixed with ceramics reinforcements. The ceramics reinforcements can improve the mechanical attributes of the titanium alloy. Selective Laser Melting (SLM) is one of the many AM processes which is able produce a near full dense metal part. Research needs to be done to understand and develop desired mechanical properties and microstructure of the TMCs fabricated by SLM. Titanium matrix composites (TMCs) will be studied in this project. Pure Ti powder and BN powder were premixed to 3d print the composite samples. Selective laser melting (SLM) process will be used to in-situ manufacture (TiN + TiB)/Ti composite samples by strengthening the titanium matrix with titanium boride (TiB) and titanium nitride (TiN) reinforcements. Composite samples with different weight fraction of BN were fabricated to determine the ideal weight fraction. After fabricating the samples using SLM, the samples were cut, mounted on a resin to carry out grinding and polishing, and etched to view the microstructure under an optical microscope. Tensile testing was done to study the mechanical properties of the composite sample. Results showed that (TiN + TiB)/Ti samples tensile strength almost doubled. However, the tradeoff of having higher tensile strength is that there is a reduction in elongation compared to titanium.